Impact of input, preservation and dilution on organic matter enrichment in lacustrine rift basin: A case study of lacustrine shale in Dehui Depression of Songliao Basin, NE China. (January 2022) - Xu, Zhengjian; Wang, Yang; Jiang, Shu; Fang, Chao; Liu, Luofu; Wu, Kangjun; Luo, Qun; Li, Xin; Chen, Yingying
Abstract: Lacustrine rift basins in Eastern China possess large amounts of petroleum, especially the shale gas and tight sand gas in deep formations, where "sweet spots" are closely related to organic-rich shale intervals. However, the OM enrichment of deep formation shale in lacustrine rift basins and the main controlling factors have not been well-researched in previous studies. The organic matter (OM) enrichment is mainly controlled by the OM input, preservation, and/or dilution. The shales deposited in deep formations of Songliao Basin, including the Jurassic Huoshiling (J3 h), Cretaceous Shahezi (K1 sh), and Yingcheng (K1 yc) formations, are evaluated as fair to excellent source rocks. Taking the shales as an example, the characters and impact of input, preservation, and dilution on OM enrichment in shales are discussed by utilizing the parameters of element concentrations and biomarkers. Results show that the OM sources are mixed sources of aquatic microorganisms and higher plant materials, and the higher plant materials are dominant. The bio-productivity were moderate to high. The paleoclimate was mainly the cold and semi-humid to semi-arid. The lake salinity was fresh-to brackish-water. The redox conditions were sub-reducing to sub-oxidizing. The dilution degree in Yingcheng was the strongest, followed by the Shahezi and Huoshiling. Consequently, the OM enrichment in the J3 h shale was called moderate bio-productivity and preservation model; the OM enrichment in the K1 sh shale was called high bio-productivity and preservation model; the OM enrichment in the K1 yc shale was named high dilution model. This study not only improves the model of OM enrichment but also provide some information for the research of "Deep time" in the Cretaceous of Songliao Basin, guiding the prediction of organic-rich shale distribution in lacustrine rift basin. Highlights: Fair to excellent hydrocarbon generation potential. Organic matter origins are mainly a mixture of aquatic microorganisms and terrestrial higher plants. Arid and cold paleoclimate and fresh- and brackish-water. Reducing to sub-reducing, sub-reducing to oxidizing, and sub-reducing to sub-oxidizing conditions. Moderate bio-productivity and preservation model, high bio-productivity and preservation model, high dilution model.